Dirna arrun “We Hold It”: Rematriating Junba with Archival Collections and Living Knowledge in the Kimberley, Northwest Australia - O’Connor, Pete Myadooma; Divilli, John Nyunjuma; Charles, Rona Goonginda; Treloyn, Sally (MUSICultures, 2025)
Since 2009–2010, practioner-custodians from Wanjina-Wunggurr First Nations in the Kimberley region of northwestern Australia have drawn upon archival materials relating to the multimodal performance-storytelling form Junba to renourish the practice and strengthen social and emotional well-being of young people in their communities. Numerous dance-songs that have not been performed for many years, some as long ago as the 1930s, others the 1960s, have re-entered the local canon. What has unfolded is a process of rematriating Junba (a process of reclaiming authority and agency over how Junba is held) from the archives of collecting institutions to the dynamic archives of knowledge in people and Country: dirna arrun (in Ungarinyin, “we hold it”). This article provides a written version of a lecture-recital presented and prepared by practitioner-custodians of Junba, O’Connor, Divilli, and Charles, together with collaborating ethnomusicologist, Treloyn, who are collectively engaged in this process of rematriation.